Pengaruh Konsentrasi Zat Pengaruh Tumbuh Giberelin Terhadap Daya Kecambah Biji Kurma Sukari (Phoenix Dactylifera L) - Reyhan Perdana Syahlindra; Nikmah Nikmah; Harlina Kusuma Tuti (Fakultas Pertanian Universitas Borobudur, 2024)
Date palm (Phoenix dactylifera L.) is a type of palm plant whose fruit is edible because it tastes sweet, has a height of about 15-25 meters and pinnate leaves with a length of 3-5 meters. Dates are a large commodity and an important crop in hot and barren areas such as Saudi Arabia, Egypt. Apart from these countries, dates are also famous in Indonesia because of their sweet taste and many benefits. Cultivation of date palms is carried out generatively through seeds, propagation of date palms through seeds is one of the main ways to get the same genetics as the parent for the cultivation process. Date seeds take 100 days or more for a success rate of 20%. Soaking with GA3 for hard-skinned seeds needs to be done to speed up the germination process. Longer soaking of the seeds is expected to increase the growth regulators absorbed by the seeds so that they can accelerate germination and increase the percentage of germination which results in increased growth. This research was conducted to determine the effect of concentration and duration of immersion of gibberellin growth regulator on the germination of Sukari date seeds. The research was carried out in the home yard of the Mampang Prapatan sub-district, South Jakarta. In April to May 2020. The experimental design carried out in this study was the factorial in randomized block design (RBD). The first factor was three kinds of gibberellin concentration (200 ppm, 400 ppm, and 600 ppm) and the second factor was three kinds of soaking time (6 hours, 12 hours, and 18 hours). The results showed that the interaction of GA3 and the duration of immersion of Sukari dates had no effect on each parameter of the observation.